Bea's own good - Talley, Linda, 1948-; Chase, Andra, 1942- (Kansas City, Mo. : MarshMedia, 1997)
A young French honeybee learns the rules to keep the honeycomb strong, to make the best honey, and to keep the bees safe. End pages feature factual information about bees, the Chateau of Villandry, and France.
5.2
K-3
Keywords: Honeybee -- Fiction; Bees -- Fiction; Honeybees -- Fiction; Bees -- Fiction; France -- Fiction; France -- Fiction